Innovación, caracterización, fitoquímicos, alteración. Extracción y caracterización de un colorante a partir del sangorache (amaranthus hybridus l.) aplicado en un yogur natural - Martínez Tocagón, Cristian Orlando (2019)
The present investigation is carried out with the objective of extracting a natural dye from flowers and stems of Sangorache (Amaranthus hybridus l) by means of the soxhlet method for the application in a natural yogurt, these parts are used because they form inflorescences whose shape is glomerular and of an intense red-violet color. What is tested for the extraction of this dye is ethyl alcohol with different concentrations at 95%, 90% and 80% with percentages of flowers and stems of (25-75%), (50-50%) and (75-25) %). The scientific innovation of this research is based on the use of the nutritional qualities and the potential that can be obtained through the leaves which is its red-violet color and its stem the dark green color. Sangorache is used for the main purpose of extracting and characterizing the dye obtained from this plant. For the research an experimental design is applied that allows to evaluate variables to differentiate the treatments with the concentrations of ethyl alcohol, the same that is an experimental design A * B with two factors (percentage of flowers and stems and concentrations of ethyl alcohol) and three levels. To know its physical-chemical and microbiological properties of the dye, we proceed to send the sample to accredited laboratories in which they show us if the dye has any alteration in the foods that are going to be used, resulting in the dye fulfilling the established parameters in the NTE INEN 2337: 2008 standard. A phytochemical analysis was carried out, which helped to determine the content of anthocyanins and other metabolites that are present in the extracted dye, by this analysis it is concluded that the dye despite providing a red-violet color, has medicinal properties and is suitable for the application in food, so it is proceeded to make the application in natural yogurt there is observed the intensity of the coloring of the extract based on sangorache.